Monoclonal antibody therapy in multiple myeloma: where do we stand and where are we going?. (March 2016) - Thanendrarajan, Sharmilan; Davies, Faith E; Morgan, Gareth J; Schinke, Carolina; Mathur, Pankaj; Heuck, Christoph J; Zangari, Maurizio; Epstein, Joshua; Yaccoby, Shmuel; Weinhold, Niels; Barlogie, Bart; van Rhee, Frits
Multiple myeloma is a plasma cell malignancy that is characterized by refractory and relapsing course of disease. Despite the introduction of high-dose chemotherapy in combination with autologous stem cell transplantation and innovative agents such as proteasome inhibitors and immunomodulatory drugs, achieving cure in multiple myeloma is a challenging endeavor. In the last couple of years, enormous advances were made in implementing monoclonal antibody therapy in multiple myeloma. A large number of preclinical and clinical studies have been introduced successfully, demonstrating a safe and efficient administration of monoclonal antibodies in multiple myeloma. In particular, the application of monoclonal antibodies in combination with immunomodulatory drugs, proteasome inhibitors, corticosteroids or conventional chemotherapy seem to be promising and will expand the treatment arsenal for patients with multiple myeloma.